Implementing Cryptocurrency Zakat Payments: An Analytical Study of the Federal Territories Islamic Religious Council Zakat Collection Centre (PPZ-MAIWP) - Muhammad Al-Husam Mohd Kamal Nazmi; Md Yazid Ahmad; Nik Abdul Rahim Nik Abdul Ghani (PT. Islamic Research Publisher, 2026)
The rapid growth of cryptocurrency and other digital assets has introduced new challenges and opportunities for zakat administration in Muslim-majority countries. In Malaysia, where digital assets are legally recognised as commodities under the existing regulatory framework, official zakat institutions have begun exploring innovative mechanisms to facilitate zakat payments using cryptocurrency. Despite this development, empirical research examining the institutional implementation of cryptocurrency zakat payments remains limited. This study aims to analyse the implementation mechanism, governance structure, and Shariah compliance of cryptocurrency zakat payments at the Federal Territories Islamic Religious Council Zakat Collection Centre (PPZ-MAIWP) through its collaboration with Sharlife Sdn. Bhd. Employing a qualitative field research approach, the study integrates document analysis, semi-structured interviews with representatives of PPZ-MAIWP and Sharlife Sdn. Bhd., and a review of relevant legal, regulatory, and Shariah literature. The findings reveal that the institutional framework developed through this collaboration provides a structured, transparent, and technologically secure mechanism for facilitating cryptocurrency zakat payments while ensuring compliance with fundamental Shariah principles, including ownership (al-milk), lawful wealth (al-māl al-mutaqawwam), and valid transfer (tamlik). The initiative has also attracted significant attention beyond Malaysia, demonstrating its potential as a model for digital zakat governance in the global Islamic finance ecosystem. Nevertheless, the study identifies the need for more comprehensive Shariah governance standards, clearer regulatory guidelines for cryptocurrency eligibility, and stronger cybersecurity safeguards to mitigate operational risks and enhance public confidence. The study concludes that cryptocurrency-based zakat payment has considerable potential to expand zakat collection, improve institutional efficiency, and strengthen the distribution of zakat funds to eligible beneficiaries (asnaf). Its primary scientific contribution lies in proposing an integrated institutional framework that combines digital financial innovation, Shariah governance, and maqāṣid al-sharīʿah principles to support the sustainable transformation of contemporary zakat management.